PENGARUH JENIS INDUSTRI, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP KARAKTERISTIK PENGUNGKAPAN CSR (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di BEI 2018 – 2020) - Muhamad Salim; Anik Malikah; Afifudin Afifudin (Universitas Islam Malang, 2021)
This study aims to determine the effect of Industry Type, Company Size and Leverage on CSR Disclosure in Manufacturing Companies listed on the Indonesia Stock Exchange in 2018 - 2020. Based on the number of calculations, 85 companies were selected as samples. The results of the analysis using multiple linear regression analysis which shows that the type of industry, company size and leverage have a significant effect on Corporate Social Responsibility simultaneously. Partially, the test results show that the type of industry and company size have a significant effect, in contrast to Leverage, which has no significant effect.Keywords: Type of Industry, Company Size, Leverage, Corporate Social Responsibility.